Pembinaaan Toleransi Antar Umat Beragama Perspektif Pendidikan Agama Islam Bagi Remaja Kota Kendari - Herman DM; Mohamad Rijal (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This research is an effort to reveal the portrait of religious tolerance among religious perspectives of Islamic religious education perspective for adolescents in Kendari Barat of Kendari. The main questions addressed in this study are (1) how to foster interfaith religious tolerance among youths in Kendari? and (2) How Islamic education is perceived by teenagers in Kendari. To address the questions, the researcher employs several research methods. The method used in data analysis is descriptive method in which the authors provide descriptive on the subject of researchers based on variable data obtained from the group of subjects studied. The findings of this study indicate that, (1) in fostering the attitude of tolerance among adherents for adolescents in of Kendari, among others, fostering adolescents not to question differences of beliefs to other religions, fostering adolescents not to disturb other followers when running religious services, fostering adolescents not to force adherents of other faiths to convert to Islam and foster adolescents in order not to force followers of other faiths to follow religious activities. While (2) Islamic education for teenagers by parents in Kendari, among others, adolescents always appreciate the elderly even though he has different religion, be gentle in family life and community, help others in need though the person is another religion, guide teenagers so as not to criticize other faiths and always build relationships with followers of other religions.